Child Mental Health and Human Capital Accumulation: The Case of ADHD Revisited - Fletcher, Jason; Wolfe, Barbara (My University, 2008)
The authors look at a sample of children with attention deficit hyperactivity disorder. They confirm and extend findings by other analysts in terms of implications for schooling, and they explore implications for human capital of siblings.